Lifestyle modification program, LIFE is LIGHT, in patients with type 2 diabetes mellitus and obesity: Results from a 48‐week, multicenter, non‐randomized, parallel‐group, open‐label study. (9th April 2021) - Galstyan, Gagik R.; Valeeva, Farida V.; Motkova, Svetlana I.; Surkova, Elena V.; Savelyeva, Larisa V.; Rudina, Larisa M.; Ramanathan, Krishnan; Sokareva, Ekaterina; Bondareva, Kristina; Shestakova, Marina V.
Abstract: Background: Obesity is a potential risk factor for development of type 2 diabetes mellitus (T2DM). To achieve long‐term weight reduction in patients with T2DM and obesity using comprehensive lifestyle management program (LMP). Materials and methods: This 48‐week interventional, multicenter, parallel‐group, open‐label study included patients aged ≥18 years with T2DM and a body mass index (BMI) of 27–40 kg/m 2 . The primary objective was to demonstrate a clinically significant weight reduction (≥5%) from baseline in intensive lifestyle modification (ILM) and standard treatment (ST) groups. Results: The ILM group ( N = 100) received recommendations for dietary and physical activity, and behavioral counseling. The ST group ( N = 30) was managed in accordance with routine T2DM clinical practice. The patients in ST group were older (60.6 ± 8.9 vs. 54.6 ± 10.2 years in ILM group); overall more than 60% were women. At Week 48, the mean reduction in body weight was 5.8% (95% confidence interval [CI]: −6.9, −4.6) and 1.2% (95% CI: −2.6, 0.2) ( p < 0.001) in the ILM and ST group, respectively. At Week 48, a weight loss of ≥5% was achieved by 50% of patients in the ILM group versus 13.3% in the ST group ( p = 0.002). The decreases in BMI, waist‐to‐hip ratio and glycated hemoglobin (HbA1c) was significantly greater in the ILM versus ST group with between‐group differences of −1.63 ( p ≤ 0.001), −0.03 ( р ≤ 0.001) and −0.69% ( p = 0.002), respectively. Conclusion: A clinically significant weight reduction (≥5%) was demonstrated in patients with obesity and T2DM with use of a comprehensive LMP, along with improvements in BMI, waist‐to‐hip ratio, and HbA1c.